Effect of Adalimumab on Refractory Arthritis in Juvenile Idiopathic Inflammatory Myopathy with Anti-MDA5 Autoantibody - Takako Miyamae; Takuma Hara; Aki Hanaya; Yumi Tani; Takayuki Kishi; Hisashi Yamanaka (Case Reports in Rheumatology)
A 10-year-old girl manifested persistent fever, skin rash, leg pain, fatigue, and joint pain. Based on muscle weakness, elevated muscle-derived enzymes, magnetic resonance imaging, and skin biopsy results, the diagnosis was juvenile idiopathic inflammatory myopathies (JIIM). Chest CT was normal; the anti-melanoma differentiation-associated protein-5 (anti-MDA5) autoantibody was positive. Initial manifestations subsided after prednisolone (PSL) and methotrexate treatment. After the PSL dosage was decreased, the patient presented with metacarpophalangeal (MCP) joint pain and swelling in both index fingers, synovial fluid, and signals on power Doppler ultrasound. The arthritis was refractory to cyclosporine and tacrolimus. Radiography showed progressive MCP joint space narrowing and joint erosion. Adalimumab was initiated 14 months after disease onset. There was a mildly increased matrix metalloproteinase-3 (MMP3) level, an erythrocyte sedimentation ratio (ESR), and a normal CRP level. Adalimumab resulted in decreased MCP joint pain and swelling. PSL was discontinued 10 months after adalimumab initiation; after 9 more months of adalimumab, there were no significant ultrasonography findings. MMP3 and ESR levels normalized during treatment. Radiography after 2 years of adalimumab showed further progressive MCP joint space narrowing restricting dorsiflexion. This report clarified that anti-MDA5-positive JIIM joint manifestations were due to active synovitis and that adalimumab is required for severe cases. Further experience is needed to determine the pathology, severity, and prognosis of this type of arthritis.